2019
DOI: 10.1016/j.chb.2019.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Feeling anxious? Perceiving anxiety in tweets using machine learning

Abstract: This study provides a predictive measurement tool to examine perceived anxiety from a longitudinal perspective, using a non-intrusive machine learning approach to scale human rating of anxiety in microblogs. Results suggest that our chosen machine learning approach depicts perceived user state-anxiety fluctuations over time, as well as mean trait anxiety. We further find a reverse relationship between perceived anxiety and outcomes such as social engagement and popularity. Implications on the individual, organ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 53 publications
0
30
0
2
Order By: Relevance
“…This particular technique is new, and it is limited to healthcare sector. In addition, the research by Kosiniski et al 2016; cited by Gruda and Hasan 2019) provided a link between machine-learning and cyber-physical systems performance. However, the article showed limited managerial inputs in SCM in terms of the applicability of this technology.…”
Section: Article De-selection Criteriamentioning
confidence: 99%
“…This particular technique is new, and it is limited to healthcare sector. In addition, the research by Kosiniski et al 2016; cited by Gruda and Hasan 2019) provided a link between machine-learning and cyber-physical systems performance. However, the article showed limited managerial inputs in SCM in terms of the applicability of this technology.…”
Section: Article De-selection Criteriamentioning
confidence: 99%
“…The algorithm was based on self-report personality trait test scores as well as our participants' social media data history. Evidence (e.g., Bollaert et al, 2019) suggested that narcissism can be successfully measured in online contexts and other studies have utilized social media posts to predict personality traits (Gruda & Hasan, 2019;Park et al, 2015;Schwartz et al, 2013). Based on a pre-annotated dataset with personality scores of our 229 participants, relevant behavioral features were extracted from users' textual content as well as profile metrics.…”
Section: Phase 1: Machine Learning Processmentioning
confidence: 99%
“…O trabalho feito por [Islam et al ] utiliza o Facebook como objeto de estudo para detecção de depressão através de técnicas de aprendizado de máquina. Em [Gruda and Hasan 2019, Sahota and Sankar 2019, Silveira et al 2018, os autores abordam a detecção da ansiedade, bipolaridade, depressão e suicídio em diferentes redes sociais e procuram entender o comportamento dos usuários presentes nessas redes sociais como forma de propor políticas que contribuam para a diminuição do volume de pessoas afetadas por estes problemas. Considerando o Reddit, os autores em [De Choudhury and De 2014] utilizam dados coletados desta rede para analisar os posts e comentários dos usuários, investigando como o grau de desinibição nos comentários e posts feitos por usuários anônimos se difere daqueles feitos pelos usuários que se identificam.…”
Section: Trabalhos Relacionadosunclassified